Rational use of diagnostic imaging in paediatrics : report of a WHO study group, meeting held in Geneva from 18 to 25 November 1985 - WHO Study Group on the Rational Use of Diagnostic Imaging in Paediatrics; World Health Organization (Geneva : World Health Organization, 1987)
Presents straightforward, precise and highly detailed advice concerning the correct and safe use of diagnostic imaging techniques in paediatric patients, including neonates. Both conventional imaging techniques and a range of new procedures are considered in detail. The objective is to make readers conscious of the many clinical and technical questions surrounding specific techniques and specific indications and then to answer these questions as clearly and authoritatively as possible. Recommended dos and donts, which represent the consensus reached by 17 international experts, are backed by reference to well over 500 published reports.
1. Introduction -- 2. The chest -- 3. The extremities -- 4. The abdomen -- 5. Skull and spine -- 6. Protection from excessive radiation exposure -- 7. Summary and conclusions -- Acknowledgements -- References
Keywords: Radiography; Radionuclide Imaging; Pharmacology; Toxicology; Clinical Technology